2002
DOI: 10.1152/ajplung.00060.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human airway epithelial cell IL-8 expression by MAP kinases

Abstract: Recent studies indicate that maximal IL-8 protein expression requires activation of NF-κB as well as activation of the MAP kinases ERK, JNK, and p38. However, the precise relationship between NF-κB transactivation and MAP kinase activation remains unclear. We examined the requirements of NF-κB, ERK, JNK, and p38 for TNF-α-induced transcription from the IL-8 promoter in a human bronchial epithelial cell line. Treatment with TNF-α induced activation of all three MAP kinases. Using a combination of chemical and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 76 publications
(101 reference statements)
10
125
1
Order By: Relevance
“…The fact that this amount of activated NF-κB, although proven to be partly due to PAR-2 activation, did not lead to secretion of IL-8 as observed in the lower enzyme concentrations puzzled us. Theoretically, as previously mentioned, purified king crab trypsin might be able to cleave PAR-2 both at activation and (Li et al, 2002).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The fact that this amount of activated NF-κB, although proven to be partly due to PAR-2 activation, did not lead to secretion of IL-8 as observed in the lower enzyme concentrations puzzled us. Theoretically, as previously mentioned, purified king crab trypsin might be able to cleave PAR-2 both at activation and (Li et al, 2002).…”
Section: Discussionmentioning
confidence: 82%
“…Research indicates that maximal IL-8 protein expression requires activation of NF-κB as well as activation of the MAP kinases ERK, JNK, and p38 (Li et al, 2002). In order to investigate the contribution of MEK/ERK , p38 and NF-κB to the observed secretion of IL-8 and by this to address the observed lack of IL-8 secretion following the generous NF-κB induction in cells stimulated by higher concentrations of purified king crab trypsin, we examined the effects of U0126 (MEK inhibitor), SB202190 (p38 inhibitor), and BAY 11-7082 (NF-κB inhibitor) in PAR-2 agonist peptide, sardine and king crab stimulated A549/NF-κB-luc cells.…”
Section: Il-8 Secretion By Purified Sardine and King Crab Trypsin Stimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that Pen c 13 induced IL-8 release in HAECs via intracellular calcium-regulated ERK activation. Proteases from other allergens, such as cockroach proteases and house dust mite Der p 3, have been shown to elicit IL-8 release by human bronchial epithelial cells via activation of PAR-2 and ERK (5, 35) and recent observations indicate that IL-8 expression in human bronchial epithelial cells requires activation of MAPKs (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The PAR-1 agonist peptide (SFLLRN), PAR-2 agonist peptide (SLIGKV), PAR-2 reverse peptide (PAR-2 RP; VKGILS), PAR-1 activation site peptide [35][36][37][38][39][40][41][42][43][44][45][46] ), and PAR-2 activation site peptide 32-45 ( 32 SSKGRSLIGKVDGT 45 ) were synthesized by Openbiosystems and purified by reversed HPLC. Abs against amino acids 42-55 of human PAR-1 (ATAP2), amino acids 37-50 of human PAR-2 (SAM11), all forms of ERK 1/2, or phosphorylated ERK 1/2 were obtained from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%